2016
DOI: 10.18549/pharmpract.2016.02.647
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of STAT medication ordering process in a community hospital

Abstract: Background:In most health care facilities, problems related to delays in STAT medication order processing time are of common concern.Objective:The purpose of this study was to evaluate processing time for STAT orders at Kimball Medical Center.Methods:All STAT orders were reviewed to determine processing time; order processing time was also stratified by physician order entry (physician entered (PE) orders vs. non-physician entered (NPE) orders). Collected data included medication ordered, indication, time orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
5
0
5
Order By: Relevance
“…We also found that turnaround times were significantly faster if the medication was available in the clinical unit, which is consistent with previously published findings. 21 …”
Section: Discussionmentioning
confidence: 99%
“…We also found that turnaround times were significantly faster if the medication was available in the clinical unit, which is consistent with previously published findings. 21 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study at Aramco Johns Hopkins in Saudi Arabia revealed a decrease in the time needed to deliver stat medications (from 59.7 min to 40.7 min) after the implementation of multiple systems, which included structured communication, an electronic inbox for stat medication orders sent by nurses to the pharmacy, and the use of a pink envelope for delivering stat medication orders [2]. Another study at the Kimball Medical Center in New Jersey revealed that the median time needed to process non-physician-entered orders was significantly less than that needed for physician-entered orders (27 min vs. 34 min) [11]. However, another study from the United States revealed that "ward bay wall charts" for documenting and communicating stat medications actually increased the median time to administration (from 94 min to 146 min, a 55% increase), which was associated with delayed medication delivery and poorer communication [3].…”
Section: Discussionmentioning
confidence: 99%
“…O serviço de distribuição correspondeu a um dos com maior impacto em termos no cumprimento dos serviços, sendo essencial para disponibilização oportuna do medicamento e segurança no processo de seu uso 20,[29][30][31] . Os resultados corroboram com a literatura que aponta melhora na execução de serviços farmacêuticos hospitalares como resultado de mudanças no sistema de distribuição de medicamentos 21,32 .…”
Section: Discussionunclassified